PENJERNIHAN AIR SUMUR MENUJU AIR LAYAK MINUM DENGAN METODA LAPISAN MULTI MEDIA ( LMM ) - Swesty, Neneng; Zein, Rahmiana; Zilfa, Z. (Jurnal Riset Kimia, 2019)
The Multi Soil layering (MSL) system is a liquid waste treatment method with the use of soil as the main medium and the organic material formed in brick and arranged in layers with a homogeneous zeolite layer. The MSL system is made of acrylic (50 x 15 x 50) cm containing a brick (4 x 9 x 15) cm and (4 x 5 x 15) cm of volcanic soil mixture as the main medium mixed with charcoal, rice husk, and iron powder (70 : 10 : 10 : 5)%, permiable layer is used zeolite (2-3) mm. The sample came from the well water of one of villager at Jati, Padang. Efficiency of SML system for aeration process on turbidity parameter with flow rate variation of 2, 4, 6, 8 mL/min reach 99,8 %, for non aeration process efficiency of turbidity decrease 88,14 %. While for the flow rate of 10, 20, 40, 80 mL/min, the efficiency of decrease for aeration at parameters Mn 66,44 %, nitrite 59,74 %, nitrate 58,34 %, turbidity 54,63 %, while in non aeration efficiency decrease turbidity reach 44,04 %, Mn 47,26 %, nitrite 49,74 %, nitrate 45,57 %. Of all efficiency values decreasing all parameters already complied drinking water quality standard according to Permenkes RI No. 492/Menkes/Per/IV/2010.